Educational Challenges at SDN 75 Bengkulu City: Overcoming Students' Learning Problems in The Digital Era - Syafitri, Sinta Dwi; Muryati, Agnes Tri; Mahendra, Yusril Isa; Nirmala, Septrisa; Karni, Asniti (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This study aims to identify the challenges faced by SDN 75 Bengkulu City in addressing student learning issues in the digital era. Digital era brings significant changes to the educational studies, including wider access to information and more interactive learning methods. However, challenges such as the digital divide, teachers' readiness, and students' adaptation to online learning remain significant obstacles. This research adopts a qualitative approach with interviews and field observations, as well as document analysis related to education policies. The findings indicate that while there have been considerable efforts to integrate technology into the learning process, the main challenges lie in limited infrastructure and teachers' ability to fully utilize technology. Therefore, continuous training for teachers and improvements in school technological facilities are essential to facilitate more effective learning.